Measuring the impact of tractor trailers on soil compaction for typical sugarcane-haulage operations in Thailand - Thungsotanon, Dithaporn; Usaborisut, Prathuang; Kuson, Pramote; Kulketwong, Chompoonud; Abdullakasim, Wanrat (My University, 2017)
Mechanization associated with operations in sugarcane production may lead to severe soil compaction. Soils may be particularly susceptible during harvesting and transport of sugarcane from the fields. A tractor towing a trailer can be a useful mean of sugarcane transport even in moist soil, but this can lead to soil compaction. In this study, the influence of tractor traffic when towing two types of trailers, i.e. a full-trailer (one on the front and two axles tandem on the rear) and a semitrailer (two axles tandem), were studied. The results showed that after the passage of a tractortowed trailer, soil bulk density in the test field was increased significantly. The passage of a tractor-towed trailer increased the penetration resistance to more than 3 MPa. The effect of a vehicle passage could reach to soil depths exceeding 45 cm, and increased as axle load increased. Analysis of the soil stresses indicated that the soil had been subjected not only to the compression stress but also the shear stress. The maximum principal stress (s1) generated by a tractor-towed semi-trailer was high. Further study should determine the thresholds for carried weight on different soil conditions in order to avoid excessive soil compaction.
Keywords: Compaction; Soil compaction; Stress state transducer; Tractor; Trailer